Luminance and chromatic visual evoked potentials in type I and type II diabetes: relationships with peripheral neuropathy - Gregori, B.; Galié, E.; Pro, S.; Clementi, A.; Accornero, N. (Neurological sciences, 2006)
The objective of the study was to investigate the subclinical visual deficit in type I and II diabetes, and its relationship with peripheral neuropathy. Thirty-two healthy volunteers, 20 patients with type I diabetes and 30 patients with type II diabetes were studied in a clinical neurophysiology setting. Luminance (VEPs) and chromatic visual evoked potentials (CVEPs) were recorded, with white-black, grey-black, red-green and blue-yellow sinusoidal gratings. The peak latencies of the VEP positive wave and CVEP negative wave were recorded. Ten patients with type I and 8 with type II diabetes had peripheral neuropathy. VEPs were slower in patients with type II diabetes and CVEPs were slower in patients with type I and type II diabetes than in controls. Blue-yellow CVEPs were slower in type II than in type I diabetes. VEPs and red-green CVEPs were slower in patients with diabetes with neuropathy than in those without. In conclusion, we found that visual system impairment differs in diabetes with and without peripheral neuropathy.